Research methodology for analyzing entrepreneurial structures’ performance indicators - Пиньковецкая, Юлия Семеновна; Pinkovetskaya, Yulia (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2015)
The paper presents a system approach for analyzing the performance indicators of small and medium enterprises as well as individual entrepreneurs forming various entrepreneurial structures. It is proposed to use mathematical tool of set theory and theory of probability for modeling entrepreneurial activities. The relationship between indicators characterizing the sets of entrepreneurial structures based on size-organizational, sectoral and territorial features is studied. The typology of indicators is given. The use of density functions of a normal distribution for describing the sets of entrepreneurial structures is shown.